Jaroms Industries Limited, a sister concern of Padma Textiles Limited - Ray, Unmesh (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Post Graduate Diploma in Knitwear Industry Management (PGDKIM), 2021.